2013
DOI: 10.1021/ie400691d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Adsorption Properties of Li1.6Mn1.6O4 Spinel

Abstract: Orthorhombic-LiMnO 2 , spinel-type Li 1.6 Mn 1.6 O 4 , and spinel MnO 2 •0.5H 2 O were synthesized via a combination of hydrothermal synthesis and solid-phase reaction. o-LiMnO 2 with different stacking fault concentrations were synthesized by controlled hydrothermal reaction using a KMnO 4 , MnCl 2 , and LiOH mixed solution. Spinel-type Li 1.6 Mn 1.6 O 4 precursor was prepared via heat treatment of o-LiMnO 2 . The effects of hydrothermal and solid-phase reaction on the structure and ionexchange properties wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(52 citation statements)
references
References 31 publications
0
45
0
Order By: Relevance
“…In addition, manganese ions in the adsorbent are dissolved out during regeneration, restricting the reuse of the adsorbents (Nishihama et al, 2011;Shi et al, 2011). Recently, in order to improve the adsorption process, several trials were reported by introducing better fabrication methods (Xiao et al, 2012(Xiao et al, , 2013, proposing a new desorption method (Ryu et al, 2013a), applying reducing agents (Intaranont et al, 2014), or using a novel adsorbent (Chitrakar et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, manganese ions in the adsorbent are dissolved out during regeneration, restricting the reuse of the adsorbents (Nishihama et al, 2011;Shi et al, 2011). Recently, in order to improve the adsorption process, several trials were reported by introducing better fabrication methods (Xiao et al, 2012(Xiao et al, , 2013, proposing a new desorption method (Ryu et al, 2013a), applying reducing agents (Intaranont et al, 2014), or using a novel adsorbent (Chitrakar et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…MnO 2 ion-sieves are the potential adsorbent materials for Li + recovery from brines because of low toxicity, low cost, and high Li + selectivity [11,12]. A series of MnO 2 ion-sieves have been synthesized from lithium manganese oxides with different Li/Mn molar ratios, namely LiMn 2 O 4 , Li 4 Mn 5 O 12 , and Li 1.6 Mn 1.6 O 4 [13][14][15][16][17][18]. However, The adsorbent materials with the powder form cannot be used directly in salt lakes because of the physical loss during postadsorption retrieval [10,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The lithium reserves in China are the world's second-largest, which are primarily distributed in the salt lakes of Qinghai and Tibet [4]. However, the ratio of magnesium to lithium in the salty brine is extremely high, making it difficult to extract and recover lithium using conventional separation technologies [5,6]. Compared with precipitation and solvent extraction methods, ion-sieve adsorption has many technical merits, such as excellent selectivity and relatively low cost [7,8], which is considered to be the most promising environmentally benign technology for extracting lithium from salt lakes [9,10].…”
Section: Introductionmentioning
confidence: 99%